PENGARUH INDEPENDENSI, KOMPETENSI, DAN PENGALAMAN KERJA TERHADAP KUALITAS AUDIT PADA BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA PERWAKILAN PROVINSI NUSA TENGGARA TIMUR - Jahormin Simarmata; Natrion; Marce Jumniati Nawa (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
The purpose of this study was to determine the effect of independence, competence, and work experience on audit quality at the Supreme Audit Agency of the Republic of Indonesia Representative of the Province of East Nusa Tenggara. The population were all the auditors who worked at the State Audit Board of East Nusa Tenggara Province. The samples used were 52 respondents from 80 respondents. The data of this study are primary data obtained through the distribution of questionnaires. The sampling technique used the Incidental Sampling method while the data processing method was multiple linear analysis with the SPSS version 24. The results of this study that independence and work experience have a significant effect on audit quality, while competence has no significant. Simultaneously that the independence, competence, and work experience have a significant effect on audit quality by 48.6%, while the remaining was caused by other factors not examined in this research